Performance characteristic of A cyclone gasifier for power generation. - Miskam, Muhammad Azman; Zainal Alauddin, Zainal Alimuddin; Mustafa, Khairil Faizi (Universiti Sains Malaysia, 2007)

(untitled)
A new technique of gasifying pulverized biomass fuel based on cyclonic motion concept is being developed for power generation.Sawdust has been used as a fuel for cyclone gasifier reactor to produced producer gases of typically 3 - 5 MJ/m3 . The work of this project involved both theoretical and experimental work to understand the operation as well as the performance and characteristics of a cyclone gasifier.